2017
DOI: 10.4081/mr.2017.7177
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical presence and distribution of ghrelin, apelin and their receptors in dog ovaries

Abstract: The activity of ghrelin, apelin and their receptors has been correlated to the control of some infectious diseases, besides the hypothesis of their role in the control of some peripheral organs, among which ovaries. The aim of the present work was to highlight the presence and distribution of ghrelin, apelin and cognate receptors in the ovaries of pregnant bitches, by means of immunohistochemical techniques. Apelin, its receptor and the receptor of ghrelin were highlighted in the corpora lutea, with a particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Ró życka et al [67] also demonstrated differences in the immunolocalization of apelin in SLCs and LLCs during the early, mid-(the highest intensity), and late luteal phases. Additionally, Pirino et al [335] showed the protein expression of the apelin system in the CL (in the cytoplasm of some LCs) from dogs' ovaries, and Pope et al [65] demonstrated the expression of apelin and APJ in mice ovaries, mainly in the periphery of the corpora lutea mass.…”
Section: Apelinmentioning
confidence: 99%
“…Ró życka et al [67] also demonstrated differences in the immunolocalization of apelin in SLCs and LLCs during the early, mid-(the highest intensity), and late luteal phases. Additionally, Pirino et al [335] showed the protein expression of the apelin system in the CL (in the cytoplasm of some LCs) from dogs' ovaries, and Pope et al [65] demonstrated the expression of apelin and APJ in mice ovaries, mainly in the periphery of the corpora lutea mass.…”
Section: Apelinmentioning
confidence: 99%